Niilismo, religião e política nos diários de Lúcio Cardoso - Diogo Andrade de Lima (2021)
The aim of this work is to investigate three main themes in Lúcio Cardoso’s diary writing. In the first chapter, the aim was to examine how nihilism, in its various manifestations, is present in his diaries. Reflecting on the reception of Nietzschean philosophy in Lúcio’s work, the possibility of transvaluing the Cardosean project was suggested, not only undertaking the diaries, but also the novels Chronicle of the murdered house and “O viajante”. In light of Cioran’s pessimistic philosophy, the presence of existential nihilism was examined in Lucio’s diaries. The second chapter focused on a study of religious matters tied to the author and present in the object of study. Supported by Berger’s and Luckmann’s considerations about socialization, as well as Bergson’s considerations regarding the relation between memory and past, the influence of Catholic childhood and the presentification of it in adult life was appraised. An examination of the Cardosean viewpoint concerning faith, the Church, original sin, the so-called “flesh problem” and Christ was carried out; likewise, there was an inspection of epistolary texts inserted in the diaries or that interact with them, enriching the author’s reflections about religion. Finally, in the third chapter, political elements found in Lúcio’s diary writing were discussed, such as his alienation from the war, his critique of democratic ideals, and his approximation with fascist thought.